De la educación y la política, al abordaje de la política pública en la formación del sujeto - Medina Ágredo, Patricia (Universidad Santiago de Cali, 2020)
Talking about education has traditionally moved on issues about pedagogy and curriculum, an aspect that has been expanding over time and the discussions about education and in particular when analyzing the implications and understandings of pedagogy and curriculum, and the questions that arise and that pass in other dimensions, for example, the educational policy that in recent decades has taken importance in the field of education. The purpose of this document is to work on the meaning of education and politics, transiting the discourse on these terms and having as a result public policies. In addition to the above, this document is based on the reflections in the teaching exercise and in coordination with education policies and practices.